Cost‐effectiveness analysis of robot‐assisted vs. open partial nephrectomy. Issue 4 (28th May 2018) - Buse, Stephan; Hach, Carolin E.; Klumpen, Phillip; Schmitz, Karoline; Mager, Rene; Mottrie, Alexandre; Haferkamp, Axel
Abstract: Background: The cost‐effectiveness of robot‐assisted partial nephrectomy (RAPN) vs. the open procedure is not established. Methods: We estimated in‐hospital complications and the cost of RAPN vs. open partial nephrectomy (OPN) using an economic model. Costs incurred both intraoperatively and in hospital were considered. US data were extracted from existing literature. Results: Mean in‐hospital costs were $14, 824 (95% CI $13, 368–$16, 898) for RAPN and $15, 094 (95% CI $13, 491–$17, 140) for OPN. Complications after RAPN occurred in 23.3% (95% CI 20.0–25.8%) and after OPN in 36.1% (95% CI 35.6–36.6%) of the patients. In a sensitivity analysis, limited centre experience was associated with relevant increase in RAPN cost and consequently in low cost‐effectiveness. Conclusions: In this economic model based on US data, RAPN resulted in nominally lower cost but fewer perioperative complications than OPN. RAPN was not cost‐effective in less experienced centres.